ANALISIS PERPINDAHAN PANAS KONVEKSI PADA PENERIMA VOLUMETRIK DI MENARA SURYA MENGGUNAKAN METODE VOLUME HINGGA - Fatahillah, Arif; Dafik, D; Amalina, Putri Nur (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2019)
In the real life, electric energy has become an essential resource which is needed by men. The commonly used fossil-based fuel which needs very long time in forming can cause some researchers try to create new energy resource which exploits solar energy. Solar tower is one of the tools which has been established by researchers. Thus, there is volumetric receiver inside the solar tower which has function as heat exchanger. Mathematic model which is employed in this research focuses on the air flow on volumetric receiver by applying finite volume method. The design is built based on wind speed and temperature around the solar tower in order to know the effect of wind speed and the temperature around toward the temperature inside the volumetric receiver. Based on the simulation result using MATLAB software, it is found that of wind speed ; and has an average temperature value on the volumetric receiver , , and with relative error . On the other hand, the effects of temperature around are about , , and with relative error .